A modified hybrid chemical vapor deposition method for the fabrication of efficient CsPbBr3 perovskite solar cells. (1st November 2021) - Ullah, Saad; Liu, Linlin; Yang, Shi-E; Liu, Ping; Guo, Haizhong; Chen, Yongsheng
Abstract: Due to its outstanding stability, all-inorganic cesium lead bromide (CsPbBr3 ) perovskite is gaining increasing attention as a functional material in photovoltaics and other optoelectronic applications. However, the preparation of high-quality CsPbBr3 films via solution processing remains a significant challenge due to the cesium precursor's low solubility in common solvents. As a result, developing viable evaporation deposition strategies is critical for increasing the photovoltaic performance of perovskite solar cells (PSCs) based on CsPbBr3 . In this paper, a modified hybrid chemical vapor deposition is applied to fabricate CsPbBr3 films, and the effects of reaction temperature and reaction time on the crystallinity, morphology, and photo-electric properties of the films are investigated. By optimizing the reaction conditions, high-quality CsPbBr3 films with good crystallinity and uniformity are successfully obtained. Based on these films, CsPbBr3 PSCs with a device configuration of fluorine-doped tin oxide/compact-TiO2 /CsPbBr3 /carbon attained impressive power conversion efficiency of 4.41% with an ultra-high open-circuit voltage ( V OC ) of 1.39 V. This demonstration suggests that the modified hybrid chemical vapor deposition strategy enables a promising fabrication route suitable for all-inorganic perovskite thin films in photovoltaic application.